2000
DOI: 10.1001/jama.284.15.1962
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Web for Medical Information by a Gastroenterology Clinic Population

Abstract: In this clinic setting, more than one quarter of gastroenterology outpatients reported having obtained medical information from the Web within the previous year. More than two thirds of patients stated they would use the Web as a medical information resource in the future. JAMA. 2000;284:1962-1964.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
60
1
7

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 4 publications
9
60
1
7
Order By: Relevance
“…In the study, younger patients and females used the Internet more frequently than other groups. This was statistically significant and consistent with previous studies (7)(8)(9). Patients with higher levels of education showed a trend toward greater Internet use, but this trend did not achieve statistical significance.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the study, younger patients and females used the Internet more frequently than other groups. This was statistically significant and consistent with previous studies (7)(8)(9). Patients with higher levels of education showed a trend toward greater Internet use, but this trend did not achieve statistical significance.…”
Section: Discussionsupporting
confidence: 90%
“…Patients might search for medical information while awaiting consultation, and the Internet serves as an easily accessible resource. Studies conducted on Internet usage by patients with gastrointestinal ailments have shown Internet usage rates ranging from 26% to 92%, with females, younger patients, and educated patients more likely to use the web (7)(8)(9)(10)(11). When searching the Internet, patients most frequently sought causes of disease and treatment options (7,12).…”
Section: Introductionmentioning
confidence: 99%
“…This finding is similar to that described in the literature, in which 60 -78% of subjects wished to have an internet source of information about the disease. 10,24,25 These data indicate that the internet will become even more important in the coming years. Although barriers to internet access still exist, we believe that they will decrease with time as technology progresses, making health-care information on the internet more common.…”
Section: Discussionmentioning
confidence: 98%
“…Patient preference for being informed of abnormal results "face to face" (5) likely reflects a desire for discussion with the physician. Electronic media, which are used by a growing number of gastroenterology patients (11), may be used to convey test results to the patient. However, these methods of communicating are impersonal and may not be appropriate for conveying sensitive information.…”
Section: Doctor-patient Communication After Endoscopy: Drowning In Inmentioning
confidence: 99%